Respostas
respondido por:
15
|3. -4. 3. 3. -4|
|2. -1. -1. 2. -1|
|1. -3. -1. 1. -3|
D=3+4-18+3-9-8
D=3+4+3-18-9-8
D=10-35
D=-25
Dx=|-1. -4. 3. -1. -4|
|-5. -1. -1. -5. -1|
|-6. -3. -1. -6. -3|
Dx=-1-24+45-18+3+20
Dx=-43+68
Dx=25
Dy=|3. -1. 3. 3. -1|
|2. -5. -1. 2. -5|
|1. -6. -1. 1. -6|
Dy=15+1-36+15-18-2
Dy=31-56
Dy=-25
Dz=|3. -4. -1. 3. -4|
|2. -1. -5. 2. -1|
|1. -3. -6. 1. -3|
Dz=18+20+6-1-45-48
Dz=44-94
Dz=-50
Dx/D=25/-25=-1
Dy/D=-25/-25=1
Dz/D=-50/-25=2
|2. -1. -1. 2. -1|
|1. -3. -1. 1. -3|
D=3+4-18+3-9-8
D=3+4+3-18-9-8
D=10-35
D=-25
Dx=|-1. -4. 3. -1. -4|
|-5. -1. -1. -5. -1|
|-6. -3. -1. -6. -3|
Dx=-1-24+45-18+3+20
Dx=-43+68
Dx=25
Dy=|3. -1. 3. 3. -1|
|2. -5. -1. 2. -5|
|1. -6. -1. 1. -6|
Dy=15+1-36+15-18-2
Dy=31-56
Dy=-25
Dz=|3. -4. -1. 3. -4|
|2. -1. -5. 2. -1|
|1. -3. -6. 1. -3|
Dz=18+20+6-1-45-48
Dz=44-94
Dz=-50
Dx/D=25/-25=-1
Dy/D=-25/-25=1
Dz/D=-50/-25=2
adrianasouza2:
Obrigado *-*
respondido por:
9
Ola Adriana
matriz A
3 -4 3 3 -4
2 -1 -1 2 -1
1 -3 -1 1 -3
det(A) = 3 + 4 - 18 + 3 - 9 - 8 = -25
matriz Ax
-1 -4 3 -1 -4
-5 -1 -1 -5 -1
-6 -3 -1 -6 -3
det(Ax) = -1 - 24 + 45 - 18 + 3 + 20 = 25
matriz Ay
3 -1 3 3 -1
2 -5 -1 2 -5
1 -6 -1 1 -6
det(Ay) = 15 + 1 - 36 + 15 - 18 - 2 = -25
matriz(Az)
3 -4 -1 3 -4
2 -1 -5 2 -1
1 -3 -6 1 -3
det(Az) = 18 + 20 + 6 - 1 - 45 - 48 = -50
solução
x = det(Ax)/det(A) = 25/-25 = -1
y = det(Ay(/det(A) = -25/-25 = 1
z = det(Az)/det(A) = -50/-25 = 2
.
matriz A
3 -4 3 3 -4
2 -1 -1 2 -1
1 -3 -1 1 -3
det(A) = 3 + 4 - 18 + 3 - 9 - 8 = -25
matriz Ax
-1 -4 3 -1 -4
-5 -1 -1 -5 -1
-6 -3 -1 -6 -3
det(Ax) = -1 - 24 + 45 - 18 + 3 + 20 = 25
matriz Ay
3 -1 3 3 -1
2 -5 -1 2 -5
1 -6 -1 1 -6
det(Ay) = 15 + 1 - 36 + 15 - 18 - 2 = -25
matriz(Az)
3 -4 -1 3 -4
2 -1 -5 2 -1
1 -3 -6 1 -3
det(Az) = 18 + 20 + 6 - 1 - 45 - 48 = -50
solução
x = det(Ax)/det(A) = 25/-25 = -1
y = det(Ay(/det(A) = -25/-25 = 1
z = det(Az)/det(A) = -50/-25 = 2
.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás